2017
DOI: 10.15171/jcvtr.2017.26
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter heart valve in valve implantation with Edwards SAPIEN bioprosthetic valve for different degenerated bioprosthetic valve positions (First Iranian ViV report with mid-term follow up)

Abstract: Introduction: After early successful experience with transcatheter aortic valve replacement (TAVR), concept of transcatheter implantation of a new valve within a failing bioprosthetic valve emerged. Valve-in-valve (ViV) implantation seems to be a simpler option for high risk surgical patients. Methods: We performed five ViV procedures in different valve positions. We included patients with failing bioprosthetic valves with high surgical risk due to concomitant comorbidities. We performed 2 transapical ViV pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…The first data of transcatheter valve-in-valve procedure in Iran was reported by Haji Zeinali et al, 17 who showed acceptable midterm results after the valve-in-valve treatment of different failing bioprosthetic valves (2 mitral, 1 pulmonary, and 2 tricuspid valves) in a case series of 5 patients. The patients had manageable postprocedural complications, including pleural effusions and transient ischemic attacks; furthermore, at follow-up, the patients had improved NYHA functional class without paravalvular leakage or valve thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…The first data of transcatheter valve-in-valve procedure in Iran was reported by Haji Zeinali et al, 17 who showed acceptable midterm results after the valve-in-valve treatment of different failing bioprosthetic valves (2 mitral, 1 pulmonary, and 2 tricuspid valves) in a case series of 5 patients. The patients had manageable postprocedural complications, including pleural effusions and transient ischemic attacks; furthermore, at follow-up, the patients had improved NYHA functional class without paravalvular leakage or valve thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the Echo assessment of multiple prostheses, the use of multiple and sometimes off-axis views is crucial to overcome the problem of acoustic shadowing, reverberations and mirror artefacts that are more pronounced for mechanical valves. Besides the classical mechanical and bioprosthetic valves, a steady increase in the number of percutaneous procedures is seen each year [64], including the complex transcatheter valve-in-valve and valve-in ring implantations in patients with documented prosthetic valve dysfunction [65]. More long-term outcome data are required in transcatheter aortic and mitral valve interventions which still carry significant peri-procedural risks and often leave varying degrees of residual paravalvular regurgitation [49,62,64].…”
Section: Multiple Prosthetic Valvesmentioning
confidence: 99%